Bahasa Indonesia, Perubahan Sosial, dan Masa Depan Bangsa - Aprinus Salam (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
There has been a significant changing on the existence and conventional function of Indonesian language. The changing of political constellation in Indonesia, and the dominance of practical and economic paradigm made the conventional function of Indonesian language experiencing constriction. In that changing, Indonesian language did not able to accommodate its some primary functions anymore. The praxis of using Indonesian language becomes such of formality-rite just for being recognized as Indonesian citizen. However, in the midst of other potential divider elements such as religion, ethnicity, or locality, it is the fact that only Indonesian language that is still able to